The dynamic p-median problem with mobile facilities. (September 2019) - Güden, Hüseyin; Süral, Haldun
Highlights: The most general version of the dynamic p-median problem is studied. Mobile and immobile facilities are considered separately and together. Distance based decision variables are used in the mathematical model of the problem. Three heuristics and a branch-and-price algorithm are developed. Extensive numerical experiments are performed. Abstract: Being motivated by real life applications in construction management, we consider the dynamic p -median problem and its extension with mobile facilities. The number of facilities changes over a planning horizon where one or more facilities can be opened, relocated, or closed in any period. The problem is to determine ( i ) facility locations, ( ii ) opening/closing times of facilities, ( iii ) routes of mobile facilities, and ( iv ) demand allocations to open facilities such that the total cost is minimized. We present a mixed integer programming formulation of the dynamic p -median problem using discretization of distances to control the locational decision variables. We develop a branch and price algorithm and constructive heuristics to solve the problem. Extensive computational results of the solution method are provided on a set of test problem instances.